Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

High-performance uranium extraction from seawater by a photothermal CNTs/bifunctional molecular sieve membrane - Haoyu Yao; Zixin Lin; Wen Guo; Xiangfeng Liang; Huizhou Liu; Haiyan Luo (Journal of Environmental Chemical Engineering, 2026)

Circulating ceramides and sphingomyelins: key biomarkers and targets in cardiovascular prevention - Shuyao Su; Wanyue Wang; Zhennan Lin; Xueli Yang; Yi Fu; Xiangfeng Lu; Fangchao Liu; Dongfeng Gu (Science China Life Sciences, 2026)

Covalent organic framework-mediated Nafion superhydrophobic coating for stabilizing the anode of aqueous zinc-ion batteries - Ling Zhong; Yimeng Yan; Zhixuan Ye; Xinxiang Zhang; Wenbin Yang; Jiaxian Zheng; Xiangfeng Lin; Linxin Zhang; Ge Zhou; Huiping Lin; Zhanhui Yuan (Chemical Engineering Journal, 2026)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Dual active sites based CsPbBr3/porous carbon nitrides S-scheme heterojunction for synergetic vanillin and hydrogen peroxide production - Hongwu Liao; Jiaxian Zheng; Yufei Huang; Xiangfeng Lin; Yusuke Yamauchi; Yusuke Asakura; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Facilitating extensive CC bond cleavage in lignin models through customized CeO2/C3N4 S-scheme heterojunction - Hongwu Liao; Chong Wang; Jiaxian Zheng; Zhuo Chen; Yulin Zhou; Chengning Ye; Xiangfeng Lin; Meng An; Yusuke Yamauchi; Yusuke Asakura; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Two-Objective Optimization of Tidal Array Micro-Sitting Accounting for Yaw Angle Effects - Can Zhang; Yichi Zhang; Jisheng Zhang; Xiaoming Cheng; Xiangfeng Lin; Chengsheng Wu; Zihan Ding (Journal of Marine Science and Engineering, 2025)
Power output and economic cost are two critical factors influencing the layout of tidal stream turbine arrays. To identify the optimal configuration, this study establishes a two-objective optimization framework that simultaneously considers these factors. Both the spatial location and yaw angle of each turbine are optimized to enhance overall power output, while the total length of submarine cables, which is used to transmit electricity from the turbines to the onshore power station, is adopted as the metric for economic cost. The Huludao water area is selected as the study domain. A 12-turbine array is examined under varying weight coefficients to investigate the trade-off between maximizing power output and minimizing economic cost. The optimization results show that submarine cable length decreases linearly as its economic weight coefficient increases, while the array’s power output exhibits a stepwise decline. This indicates that, with carefully chosen weight coefficients, economic costs can be significantly reduced without a proportional sacrifice in power output. Furthermore, increasing the number of turbines connected by a single cable not only enhances power output but also reduces total cable length, thereby improving the overall profitability of the optimized array layout.

Experimental analysis and proposal of semi-empirical prediction model on tidal stream turbine induced local scour subjected to wave-current loading - Xu Deng; Xiangfeng Lin; Jisheng Zhang; Siyuan Liu; Hao Chen; Shibo Zhang; Yiwei Qiu; Zihan Ding (Ocean Engineering, 2025)

Enhanced uranium extraction from seawater using bifunctional-modified molecular sieves with high selectivity and adsorption capacity - Wen Guo; Zixin Lin; Kun Jiang; Hao Li; Xiangfeng Liang; Weizhong An; Huizhou Liu; Haiyan Luo; Haoyu Yao (Desalination, 2025)

Quantitational life cycle assessment of Effluent-Energy-Carbon synergies and trade-offs in drinking water treatment plant upgrades - Yumeng Zhang; Zongqi Ding; Zewei Lin; Shoubin Chen; Shunjian Cheng; Kaiming Peng; Ru Guo; Xiangfeng Huang; Chen Cai; Jia Liu (Journal of Water Process Engineering, 2025)

Experimental investigations in the effect of passive gyro stabilizers on the pitch motion of a semi-submersible floating wind turbine - Junlei Wang; Haoran Li; Jisheng Zhang; Dawei Guan; Xiangfeng Lin; Hao Chen (Ocean Engineering, 2025)

Investigating Tidal Stream Turbine Array Performance Considering Effects of Number of Turbines, Array Layouts, and Yaw Angles - Can Zhang; Kai Zhang; Xiaoming Cheng; Xiangfeng Lin; Jisheng Zhang; Chengsheng Wu; Zhihao Ren (Journal of Marine Science and Engineering, 2024)
The performance of a tidal stream turbine array can be affected by numerous factors. Investigating the connection between array power production and these factors will be helpful in improving the development of tidal stream energy. This study investigates the impact of array layout, turbine number, and yaw angles on turbine array performance using an open-source coastal ocean modelling system. The results show that the total power output of the turbine array rises with the number of turbines. Under realistic conditions, there are not many differences in power output between aligned and staggered turbine array configurations. By extending the distance between the turbines, the array power output can be improved in both layouts. It appears that considering each turbine’s yaw angle can improve array power generation, since the downstream turbines will greatly benefit from the steering wake of the upstream turbines. Furthermore, using a gradient-based optimization algorithm to simultaneously adjust the yaw angles and turbine positions will boost the turbine array’s efficiency more than just optimizing the turbine position alone.

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

Internal solitary wave-induced soil responses and its effects on seabed instability in the South China Sea - Linlong Tong; Jisheng Zhang; Ning Chen; Xiangfeng Lin; Rui He; Lei Sun (Ocean Engineering, 2024)

Bio-based tin phytate interface assembled bismuth oxychloride for enhanced flame retardancy and smoke suppression in polyvinyl chloride coatings - Feiyang Cheng; Xiangfeng Zhu; Bokun Lin; Chen Shi; Jian Han (Journal of Cleaner Production, 2024)

Metabolomics signature of blood pressure salt sensitivity and its link to cardiovascular disease: A dietary salt-intervention trial - Zhennan Lin; Jianxin Li; Fangchao Liu; Jie Cao; Shufeng Chen; Jichun Chen; Keyong Huang; Yaqin Wang; Hongfan Li; Yan Wang; Jianfeng Huang; Dongfeng Gu; et al. (Science China Life Sciences, 2024)

Three-dimensional freeze-casting solar evaporator for highly efficient water evaporation and high salinity desalination - Bo Li; Mengxiao Lin; Changwei Cheng; Xiangfeng Li (Desalination, 2024)

Fully Coupled Hydrodynamic–Mooring–Motion Response Model for Semi-Submersible Tidal Stream Turbine Based on Actuation Line Method - Guohui Wang; Jisheng Zhang; Xiangfeng Lin; Hao Chen; Fangyu Wang; Siyuan Liu (Journal of Marine Science and Engineering, 2024)
The modeling of floating tidal stream energy turbine (FTSET) systems demands significant computational resources, especially when incorporating fully coupled models that integrate hydrodynamics, mooring, motion response, and their interactions. In this study, a novel hybrid numerical model for FTSET systems has been developed, utilizing the open-source software OpenFOAM. The hydrodynamic characteristics of three-bladed vertical-axis turbines are simulated in steady, three-dimensional wave–current numerical tanks using an unsteady actuator line method (UALM). The interFoam two-phase Navier–Stokes solver within OpenFOAM is utilized to manage the kinematic characteristics of the floating platform. Mooring dynamics are addressed using the mass–spring–damper model (MoorDyn), and turbine wake dynamics are resolved using a buoyancy-modified RANS turbulence model. The comprehensive model can simulate wave, flow, mooring dynamics, platform motion, and the interactions between the turbine and platform within FTSET systems. To validate the model, several scenarios are analyzed, and experiments are conducted to validate the numerical results. The model accurately predicts platform motion responses and mooring line tensions, especially under wave–current conditions, capturing the interconnected effects of platform motion during turbine rotation. Additionally, the model extends predictions of turbine–platform wake development and interaction.

Experimental investigation of motion response and mooring load of semi-submersible tidal stream energy turbine under wave-current interactions - Guohui Wang; Jisheng Zhang; Bohua Lu; Xiangfeng Lin; Fangyu Wang; Siyuan Liu (Ocean Engineering, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Scour processes around a horizontal axial tidal stream turbine supported by the tripod foundation - Xiangfeng Lin; Jisheng Zhang; Dawei Guan; Jinhai Zheng; Yuquan Zhang; Emmanuel Fernandez-Rodriguez; Luchao Gao (Ocean Engineering, 2024)

The genetic link between lode and disseminated gold ores and relationship between hypozonal and mesozonal deposits: A case study of the Yanzigou orogenic gold deposit, northwestern Yangtze Craton, China - QiYi Ma; HeSen Zhao; Lin Yang; ShuFei Liu; XiangFeng Song; YuanLiang Yang; XueFeng Deng; Jie Zhang; JiaZhong Chen; JinZhong Li; QingFei Wang (Journal of Asian Earth Sciences, 2024)

Structural design of Janus lamellar membrane based on bismuth oxychloride for comprehensive solar energy utilization - Weiming Zhou; Hongqiang Huang; Chong Wang; Liwei Wang; Xiangfeng Lin; Yusuke Asakura; Yusuke Yamauchi; Sameh M. Osman; Zhanhui Yuan (Chemical Engineering Journal, 2024)

Performance and wake interaction between two aligned vertical axis turbines - Xiangfeng Lin; Jisheng Zhang; Jinhai Zheng; Siyuan Liu (Ocean Engineering, 2024)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Experimental investigation of wake and thrust characteristics of a small-scale tidal stream turbine array - Jisheng Zhang; Guohui Wang; Xiangfeng Lin; Yudi Zhou; Risheng Wang; Hao Chen (Ocean Engineering, 2023)

Semi-theoretical prediction for equilibrium scour depth of a mono-pile supported tidal stream turbine - Xiangfeng Lin; Jisheng Zhang; Jinhai Zheng; Dawei Guan; Risheng Wang (Ocean Engineering, 2023)

Composition, Distribution, and Source Apportionment of Organochlorine Pesticides (OCPs) in Soil of a Chemical Industrial Park and its Surrounding in the Northeast of Qinghai-Tibet Plateau - Xiaojun Li; Lixia Cao; Xin Lin; Wanlong Fu; Zongqiang Gong; Xiangfeng Zeng; Huajun Fang; Zhiheng Li (Water, Air, & Soil Pollution, 2023)

Super-tough and self-healable all-cellulose-based electrolyte for fast degradable quasi-solid-state supercapacitor - Xiaobo Lin; Mengying Wang; Junchai Zhao; Xiangfeng Wu; Jixing Xie; Jinhui Yang (Carbohydrate Polymers, 2023)

Scour processes around a mono-pile foundation under bi-directional flow considering effects from a rotating turbine - Xiangfeng Lin; Jisheng Zhang; Dawei Guan; Jinhai Zheng; Hailong Wang; Bo Liu (Ocean Engineering, 2023)

Experimental study on failure law of subgrade concrete with different damage base - Xiangfeng Lv; Lingfeng Meng; Xin Lin; Xuan Ji; Yahan Yang (European Journal of Environmental and Civil Engineering, 2023)

The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults - Zhennan Lin; Shufeng Chen; Fangchao Liu; Jianxin Li; Jie Cao; Keyong Huang; Fengchao Liang; Jichun Chen; Hongfan Li; Jianfeng Huang; Dongsheng Hu; Chong Shen; et al. (Environmental Pollution, 2023)

Soil organic carbon and total nitrogen stocks in alpine ecosystems of Altun Mountain National Nature Reserve in dry China - Zhenzhen Zhao; Xiangfeng Zhang; Shikui Dong; Yu Wu; Shiliang Liu; Xukun Su; Xuexia Wang; Yong Zhang; Lin Tang (Environmental Monitoring and Assessment, 2019)

A novel malic enzyme gene, Mime2, from Mortierella isabellina M6-22 contributes to lipid accumulation - Shan Li; Lingyan Li; Xiangfeng Xiong; Xiuling Ji; Yunlin Wei; Lianbing Lin; Qi Zhang (Biotechnology Letters, 2018)

Co and Fe-catalysts supported on sepiolite: effects of preparation conditions on their catalytic behaviors in high temperature gas flow treatment of dye - Xiangfeng Lin; Jian Fang; Menglin Chen; Zhi Huang; Chengyuan Su (Environmental Science and Pollution Research, 2016)

Protective effect of myokine IL-15 against H2O2-mediated oxidative stress in skeletal muscle cells - Fengna Li; Yinghui Li; Yulong Tang; Binbin Lin; Xiangfeng Kong; Oso Abimbola Oladele; Yulong Yin (Molecular Biology Reports, 2014)

Myokine IL-15 regulates the crosstalk of co-cultured porcine skeletal muscle satellite cells and preadipocytes - Yinghui Li; Fengna Li; Binbin Lin; Xiangfeng Kong; Yulong Tang; Yulong Yin (Molecular Biology Reports, 2014)

The effect of regional ocean-atmosphere coupling on the long-term variability in the Pacific Ocean - Lin Feng; Dexing Wu; Xiaopei Lin; Xiangfeng Meng (Advances in Atmospheric Sciences, 2010)

A further investigation of the decadal variation of ENSO characteristics with instability analysis - Xiangfeng Meng; Dexing Wu; Xiaopei Lin; Jian Lan (Advances in Atmospheric Sciences, 2006)